An Examination of How Counselor Professionals Perceive the Role of Ict in Making Counseling Services More Accessible and Inclusive - Hassan, Ahmed Taiye; Bolaji, Hameed Olamilekan; Abdulkareem , Habibat Bolanle (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study scrutinizes counselors perceptions regarding the role of Information and Communication Technology (ICT) in advancing accessibility and inclusivity within Counselling services. A total of 159 counselor professionals participated in the survey, with 124 males and 35 females. The analysis of mean scores displayed a noteworthy variance between male (M = 3.845, SD = 1.39841) and female (M = 3.50013, SD = 1.50923) counsellor professionals' perceptions regarding ICT's influence on enhancing accessibility and inclusivity. The statistical examination utilizing an ANOVA test indicated a non-significant difference between the perceptions of male and female professionals (F-cal. = 1.726, df_between = 3, df_within = 2, p = .415). Consequently, the null hypothesis revealed no significant variance in perceptions based on gender was accepted.